2018
DOI: 10.1053/j.sodo.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in orthodontic pain: Clinical implications and pharmacological management

Abstract: Pain is a bio-physiological phenomenon characterized by a circadian rhythm. A better understanding of diurnal variability in orthodontic pain perception would not only enhance our knowledge about how orthodontic pain intensity fluctuates over the 24-h day, but it also has great potential to improve the clinical management of orthodontic pain. Since the administration timing of pharmacological interventions has a direct influence on their effectiveness, a sound knowledge of the timing of peak pain intensity wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Some controversy exists regarding differences in pain perception between the sexes. Evidence showing no differences in perception [7,9,11,13] and females experiencing greater levels of pain [22,23] is available. Fixed orthodontic appliances have been associated with pain causation in almost all studies, but data for pain perception using clear aligners is less in comparison.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Some controversy exists regarding differences in pain perception between the sexes. Evidence showing no differences in perception [7,9,11,13] and females experiencing greater levels of pain [22,23] is available. Fixed orthodontic appliances have been associated with pain causation in almost all studies, but data for pain perception using clear aligners is less in comparison.…”
Section: Background and Aimsmentioning
confidence: 99%
“… Thus, by eliminating the conventional 6–8 hourly intake of analgesics, the understanding of diurnal fluctuations in pain might not only boost the effectiveness but also limit adverse effects. [ 21 ] In a trial performed on healthy subjects, pain threshold was seen to rise more quickly and significantly during the day when a placebo was labeled as an analgesic than it does at night. This highlights the importance of the timing of placebo administration in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that the intensity of orthodontic pain fluctuates over the course of a day and this factor may cause a contradiction in the results of pain studies. 20,21 The debonding procedures in this study were always performed at mid-day; thus, the potential effect of diurnal variation was prevented. When the data was obtained, it was observed that the pain scores of the control side were already lower in most of the patients.…”
Section: Discussionmentioning
confidence: 99%